Contractual Behavior of Key Participant in Managing Green Office Building Projects. Issue 1 (1st October 2022) - Azmi, Siti Haizan; Adnan, Hamimah; Hasim, Mohamad Sufian; Mustapha, Arniatul Aiza; Wan Ismail, Wan Norizan
Abstract: In order to improve the performance of green office building projects, proper contractual behaviour of key participants is perceived as one of the best initiatives, given that it serves as the primary function in guiding the smooth management of green office building projects. This paper aims to identify the criteria in managing green office building projects. It was found that this reports on the results of the content analysis which collected data on design and features of green office building implemented by the designers. A list of GBI -Certified Green Office Buildings under New Construction Category in Malaysia was assessed. Five (5) numbers of office buildings in Klang Valley and Putrajaya area were selected to present features of green office buildings applied by the designer to fulfil the green building criteria hence achieving GBI certification. The features of each green building obtained from various relevant websites were compiled based on the six (6) criteria listed under GBI. Though the system and materials might be slightly different from one green buildings to another, there are similarities in terms design principal; by incorporating advanced green technologies, sustainable energy solutions, innovative energy management systems and rainwater harvesting systems into the design. Thorough consideration has been given by the project team to produce a building that is environmentally, socially and economically friendly. This is achieved by enhancing good passive designs and integrating active (mechanical and electrical) design and system to deliver and to offer significant long-term comfort and savings for the building owners and occupants.